Transparent conductive electrodes from graphene/PEDOT:PSS hybrid inks for ultrathin organic photodetectors - Liu, Zhaoyang; Parvez, Khaled; Li, Rongjin; Dong, Renhao; Feng, Xinliang; Muellen, Klaus (Advanced Materials, 2015)
A novel solution fabrication of largearea, highly conductive graphene films by spray-coating of a hybrid ink of exfoliated graphene (EG)/poly(3,4-ethylene dioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) (PH1000) is demonstrated. The fabricated graphene films exhibit excellent mechanical properties, thus enabling their application as bottom electrodes in ultrathin organic photodetector devices with performance comparable to that of the state-of-the-art Si-based inorganic photodetectors. (Graph Presented).
CRIS-Team Scopus Importer:2023-03-20
Keywords: Electrochemically exfoliated graphene; Organic photodetectors; Spray-coating; Transparent conductive electrodes